Expression of Myosin Heavy Chain and Some Energy Metabolism-Related Genes in the Longissimus Dorsi Muscle of Krškopolje Pigs: Effect of the Production System - Fazarinc, Gregor; Vrecl, Milka; Poklukar, Klavdija; Škrlep, Martin; Batorek-Lukač, Nina; Brankovič, Jana; Tomažin, Urška; Čandek-Potokar, Marjeta (Frontiers in Veterinary Science, 2020)
The Slovenian Krškopolje pig is the only preserved local autochthonous breed, appreciated mainly for its good meat quality and considered more appropriate for processing into dry-cured products. However, the biological characteristics of the skeletal myofibers of the Krškopolje breed, specifically the heavy myosin chain-based contractile and metabolic phenotypes that could affect meat quality, have not been established under different husbandry systems. The breed is generally maintained in either conventional indoor or organic systems. In the present study, the morphological, contractile, and metabolic properties of myofibers of the longissimus dorsi muscle were compared between animals reared in either an organic or a conventional indoor system. The myofibers were studied using immunohistochemical and succinate dehydrogenase (SDH) activity-based classification, histomorphometric assessment, and qPCR. Results revealed that the organic production system influenced the composition of the longissimus dorsi myofiber type, characterized by a smaller myofiber cross-sectional area, a shift toward oxidative (SDH-positive) myofiber types, increased relative expression of myosin heavy chain (MyHC) isoforms I, IIa, and IIx, and downregulation of MyHC IIb. On the contrary, no apparent effect was observed on the metabolic phenotype of the myofiber as assessed through relative mRNA expression of energy metabolism-related genes (peroxisome proliferator-activated receptor gamma, coactivator 1 alpha (PGC-1α), peroxisome proliferator-activated receptor gamma (PPARγ), lipoprotein-lipase (LPL), carnitine palmitoyltransferase 1B (CPT1B), glycogen synthase 1 (GYS1), hexokinase 2 (HK2), and fatty acid synthase (FASN)). Differences in MyHC expression were largely corroborated by the histochemical classification, indicating that the contractile protein content is directly regulated by the MyHC genes. A correlation between the muscle contractile and metabolic phenotypes was not established, except for that between the HK2 and MyHC I genes. In conclusion, the present study showed an evident effect of rearing on the longissimus dorsi myofiber contractile phenotype but not the metabolic phenotype. Moreover, obtained data suggest that rearing the Krškopolje pig breed in a conventional system would result in an increased fiber size and a greater proportion of type IIb myofibers, which are known to be negatively correlated with some meat quality traits.